4G mobile phone radiation alters some immunogenic and vascular gene expressions, and gross and microscopic and biochemical parameters in the chick embryo model - Md. Sadequl Islam; Md. Mominul Islam; Md. Moshiur Rahman; Khaleda Islam (Veterinary Medicine and Science, 2023)
Abstract Background The risks to human health have grown over the past 10 years due to the excessive use of mobile phones. Objectives The study was designed to determine the harmful effects of 4G mobile phone radiation on the expression of immunogenic and vascular genes and gross, microscopic and biochemical alterations in the development of chicken embryos. Methods Sixty individuals in the exposure group were subjected to mobile phones with a specific absorption rate of 1.4 W/kg and a frequency of 2100 MHz positioned at a distance of 12 cm in the incubator for 60 min/night for 14 days. The histopathological examination involved hematoxylin and eosin staining, whereas cresyl violet staining was used to evaluate the condition and number of neurons in the brain. The biochemical parameters of amniotic fluid were analysed using the photometry method, and the expression of VEGF‐A and immunity genes (AvBD9, IL6) was measured using the real‐time PCR (qPCR) technique. Results Compared to the control, the exposure group's body weight and length significantly decreased (p < 0.05). Subcutaneous bleeding was seen in the exposure group. Urea, creatinine, alkaline phosphatase, aspartate aminotransferase and alanine aminotransferase levels were all significantly higher than in the control group (p < 0.05). The exposed group showed pathological lesions in the liver and degenerated neurons with lightly stained nuclei in the cerebral cortex. Hyperchromatic neurons were significantly higher in the exposure group (58.8 ± 2.28) compared to the control (6.6 ± 0.44) (p < 0.05). 4G exposure reduced lymphocyte count in the caecal tonsil (86.8 ± 5.38) compared to the control (147.2 ± 9.06) (p < 0.05). Vascular gene mRNA expression was higher, but immune gene expression was lower in the exposed group. Conclusion Exposure to mobile phone radiation may result in gross, microscopic and biochemical changes, as well as alterations in gene expression that could hinder embryonic development.